Stochastic Modeling And Analysis of A Repairable Single Unit Systems (International Journal of Engineering and Computer Science, 2024)
In this paper we study the stochastic modeling and analysis of a repairable single unit system using Weibull distribution as it models a broad range of random variables,largely in the nature of a time to failure or time between events.Here we have considered three types of failuresabrupt, wear-out, and intermittent failures and concept of MOT(Maximum operation time) in which system goes under preventive maintenence.It is assumed that all types of failure and repair rates follow the Weibull distribution, and a single repairman can attend to all kinds of failures and preventive maintenance. By employing Semi-Markov, Regenerative Point Techniques and the Weibull distribution various system performance measures, cost analysis and busy period analysis also examined in this model. In additionally, by using some system performance measures we provide the numerical illustration with numerically and graphically